Monitoring training load in handcycling: A case study - Zeller, S.; Abel, T.; Strueder, H. K. (The Journal of Strength and Conditioning Research, 2017)
The aim of this study was to analyze the training intensity distribution (TID) and the total training load (TTL) for the first time in handcycling of a multiple female Paralympic medalist (lesion level: L2-3 incomplete, ASIA C, classification: WH5). This study focuses on the preparation and the competitive period of the 2015 season. The athlete completed 194 handcycling training sessions in a time of 433:53 hours, covering a total distance of 10.190 km. An average training week consisted of 9:38 ± 4:50 hours of training during 4.3 ± 1.5 training sessions. Training was categorized according to the 3-zone intensity scale (zone 1: below blood lactate levels of 2 mmol/L; zone 2: between 2 mmol/L and 4 mmol/L; and zone 3: above 4 mmol/L). The average TID during the observation was 71.6 ± 14.9% in zone 1, 15.2 ± 8.0% in zone 2, and 13.1 ± 5.5% in zone 3. The analysis of TID throughout the season demonstrates a tendency toward a greater volume in zone 2 than the recommendations in the literature. The mean TTL throughout the season was 804 ± 399 arbitrary units. During the investigation, the performance capacity in the incremental exercise test analog to 4 mmol/L increased by 19% (150-181 W), whereas the peak power output improved by 22% (180-200 W). Currently, no general guideline for the TTL and TID in paraplegic endurance athletes can be given.